2019
DOI: 10.1186/s12931-019-1227-3
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response to inhaled endotoxin does not correlate with airway response

Abstract: BackgroundEndotoxin is a component of particulate matter linked to respiratory disease. Our group has shown that experimental endotoxin inhalation challenge reproducibly triggers neutrophilic inflammation in the airways and in peripheral blood. Sputum induction is currently the only available method for assessing airway neutrophilia but is laborious and time-consuming. This analysis examined the correlation between systemic and airway inflammatory responses to endotoxin to determine if peripheral blood could s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Placebo-controlled trials have demonstrated that CXC chemokine receptor 2 antagonists reduce blood neutrophil counts in patients with severe neutrophilic asthma; however, there was no associated improvement in terms of asthma control, lung function, or reduced exacerbation rates in those studies. 36 , 37 This suggests that a reduction in blood neutrophil counts may not be correlated with a reduction in airway neutrophil numbers or airway inflammation, 38 , 39 limiting the accuracy of this biomarker for monitoring or predicting response to therapy. The aforementioned results call into question the role of circulating neutrophils in asthma and the extent to which non–type 2 asthma is driven by neutrophilic inflammation.…”
Section: Inflammatory Traitsmentioning
confidence: 99%
“…Placebo-controlled trials have demonstrated that CXC chemokine receptor 2 antagonists reduce blood neutrophil counts in patients with severe neutrophilic asthma; however, there was no associated improvement in terms of asthma control, lung function, or reduced exacerbation rates in those studies. 36 , 37 This suggests that a reduction in blood neutrophil counts may not be correlated with a reduction in airway neutrophil numbers or airway inflammation, 38 , 39 limiting the accuracy of this biomarker for monitoring or predicting response to therapy. The aforementioned results call into question the role of circulating neutrophils in asthma and the extent to which non–type 2 asthma is driven by neutrophilic inflammation.…”
Section: Inflammatory Traitsmentioning
confidence: 99%